ANALISIS PENGARUH KUALITAS LAYANAN, KEPUASAN PELANGGAN DAN CITRA TERHADAP LOYALITAS PELANGGAN PT. SUMBER ALFARIA TRIJAYA (ALFAMART) SEMARANG (Students' Journal of Economic and Management, 2014)
This study aims to determine the effect of service quality , customer satisfaction and corporate image effect on customer loyalty PT . Sources AlfariaTrijaya( Alfamart ) .This type of research is qualitative research , the technique of collecting data through questionnaires . The sampling technique using purposive sampling technique in which the sample collection elements are included in the sample was done on purpose , with a note that the sample representative or representative of the population . ( J. Soepranto , 2002:84 ) . The method of analysis used in this study is regression analysis , the validity, reliability, and classic asumtion examination .So the conclusion from the analysis above is that if the variable quality of service , customer satisfaction and corporate image , the better the effectiveness of behavior will increase customer loyalty and sales will increase as well.Based on the result of this research,recomendedfor employees of the service should be fast and spry , especially in the handling of customer complaints or visitors with ready and provide accurate information to customers or visitors , so that the consumer feels good service Alfamart Semarang .Discount on price can be done as often as possible , because it can attract consumers , such as price discount can be done at certain times , so that consumers feel pampered with lots of discount prices .Future studies are expected to be added in addition to the factors of service quality , customer satisfaction and corporate image as a factor Key words: quality of service , customer satisfaction , corporate image , and customer loyalty